Outlining a methodological pathway to improve the global seagrass map - Pittman, SJ; Thapa, B; Roelfsema, C; Say, C; Baez, S; Jensen, K (2022)
This project reports on seagrass mapping activities and methodology through a comprehensive global review of expert knowledge and the published literature in the past decade (2012-2021). The aim is to identify geographical data gaps, barriers to progress, associated mapping costs and to evaluate potential solutions for mapping seagrass at a global scale. This targeted information synthesis is intended to improve the understanding of future seagrass mapping needs and identify a rapid, standardized, and cost-effective path forward to address data gaps in equatorial waters with potential for global application.